2018
DOI: 10.1620/tjem.245.231
|View full text |Cite
|
Sign up to set email alerts
|

Agent-Based Modeling and Simulation of Nosocomial Infection among Healthcare Workers during Ebola Virus Disease Outbreak in Sierra Leone

Abstract: Healthcare workers (HCWs) are often exposed to nosocomial infection when caring for patients with Ebola Virus Disease (EVD). During the 2014-2016 EVD outbreak in West Africa, more than 200 HCWs died of EVD in Sierra Leone. To determine the factors that are important for preventing infection among HCWs during EVD outbreak, we used agent-based modeling and simulation (ABMS) by focusing on education, training and performance of HCWs. Here, we assumed 1, 000 HCWs as "agents" to analyze their behavior within a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The health workforce density was 2.2 per 10,000 population which was below WHO’s recommendation of 4.45 per 1000 [ 10 ]. A total of 221 healthcare workers (HCWs) died of EVD from the start of the outbreak on May 25, 2014 unto November 7, 2015 [ 11 ]. The understaffed healthcare system was further weakened, adding extra burden on the HCWs which led to increased exhaustion and fatal mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…The health workforce density was 2.2 per 10,000 population which was below WHO’s recommendation of 4.45 per 1000 [ 10 ]. A total of 221 healthcare workers (HCWs) died of EVD from the start of the outbreak on May 25, 2014 unto November 7, 2015 [ 11 ]. The understaffed healthcare system was further weakened, adding extra burden on the HCWs which led to increased exhaustion and fatal mistakes.…”
Section: Introductionmentioning
confidence: 99%
“…In the education module, HCWs are separated into several types according to their academic certificate and their willingness to work. The arrows in Fig 3 represent the possible transitions and their shifting mechanism follows the rules presented in the earlier study [ 36 ]. We mainly focus on the pre-deployment training which prepared for HCW in the Ebola affected area.…”
Section: Methodsmentioning
confidence: 99%
“…Jones-Konneh et al (2017) reviewed the trend of new patients and deaths by Ebola virus disease (EVD) and the countermeasures of affected Sierra Leone, suggesting the importance of intensive education to comply with the infection control and prevention. Jones-Konneh et al (2018) further extrapolated this notion to an agent-based simulation model of healthcare workers' attitude and found that seeking training at the time of outbreak and appropriate care procedure have a greater effect on reducing the number of health care workers infected during EVD outbreak, while initial education alone cannot prevent nosocomial infection. Saitoh et al (2015) recalled the awareness of leptospirosis as a re-emerging zoonosis, that might appear with higher prevalence when flood occurs through the report of four cases.…”
Section: Articles Related With Geje In Tjem After 2011mentioning
confidence: 99%